2020
DOI: 10.3390/coatings10090827
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Properties and In Vitro Antifungal Evaluation of Samarium Doped Hydroxyapatite Coatings

Abstract: Hydroxyapatite (HAp) and samarium doped hydroxyapatite, Ca10−xSmx(PO4)6(OH)2, xSm = 0.05, (5SmHAp), coatings were prepared by sol-gel process using the dip coating method. The stability of 5SmHAp suspension was evaluated by ultrasound measurements. Fourier transform infrared spectroscopy (FTIR) was used to examine the optical characteristics of HAp and 5SmHAp nanoparticles in suspension and coatings. The FTIR analysis revealed the presence of the functional groups specific to the structure of hydroxyapatite in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 63 publications
8
25
0
Order By: Relevance
“…More than that, the CLSM investigation showed that the few adhered C. albicans cells did not undergo transformation into their filamentous form, hence demonstrating that C. albicans were unable to evolve into their biofilm phenotype on the 10Ce-HAp surfaces [59]. These results are in good agreement with SEM visualization as well as the results of the quantitative antifungal assay and with previously reported studies regarding the antifungal properties of composite layers [60,61].…”
Section: Resultssupporting
confidence: 89%
“…More than that, the CLSM investigation showed that the few adhered C. albicans cells did not undergo transformation into their filamentous form, hence demonstrating that C. albicans were unable to evolve into their biofilm phenotype on the 10Ce-HAp surfaces [59]. These results are in good agreement with SEM visualization as well as the results of the quantitative antifungal assay and with previously reported studies regarding the antifungal properties of composite layers [60,61].…”
Section: Resultssupporting
confidence: 89%
“…These results are in good agreement with other similar studies regarding the potential antimicrobial activity of samarium ions or samarium based composites [27,29,[53][54][55][56][57][58]. Moreover, the quantitative assays were in good agreement with the results obtained in the qualitative studies performed on 5Sm-HAp suspension, target and coatings.…”
Section: Resultssupporting
confidence: 91%
“…Even for these two cases, it is possible to attain a better evolution at longer testing intervals. Overall, the LIVE/DEAD assay confirms the beneficial influence of Sm on the cells development in simulating conditions, as it was also reported by other researchers [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 87%
“…Ershad et al [ 33 ] studied melt-derived bioactive glasses with up to 4 wt.% Sm 2 O 3 ; they found that nucleation and crystal growth temperature decrease, while bioactivity and mechanical properties improve with Sm 2 O 3 concentration increasing. Sm-doped thin films were prepared from the desire to ensure two key features contributing to a better outcome following bone graft implantation: rapid osseointegration and infection avoidance; the tests evidenced antifungal properties, simultaneously with lack of toxicity against regular cell lines for Sm contents below 1 mol% [ 34 , 35 ]. Moreover, 153 Sm isotope was demonstrated to be an efficient radiotracer [ 36 ] and helpful agent for nuclear therapy through beta emission [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%